On the effects of the law of distress and the feudal rule as regards improvements in the relations between landlord and tenant - Sproule, John (Statistical and Social Inquiry Society of Ireland, 1869)
The laws affecting the relations between landlord and tenant have so frequently been discussed by the members of the Statistical Society, that some curiosity may naturally be excited by the subject being again brought forward, as to whether anything novel can now be advanced upon it. It is therefore not without some hesitation that I now venture to introduce it, more especially as much that I have to say has again and again been enunciated from this place with a degree of authority to which I cannot lay claim. The subject is, however, of so much importance, and so great have been the difficulties interposed in the way of properly dealing with it by extravagant and unreasonable demands, that any attempt at simplifying the matter is, at all events, deserving of consideration.
Read Tuesday, 18th February, 1868
Keywords: Irish agriculture; Law of distress; Feudal rule; 314.15